2011
DOI: 10.1021/ic2013478
|View full text |Cite
|
Sign up to set email alerts
|

Two Open-Framework Germanates with Nickel Complexes Incorporated into the Framework

Abstract: Two open-framework germanates, SUT-1 and SUT-2, have been synthesized under hydrothermal conditions using ethylenediamine (en, H(2)NCH(2)CH(2)NH(2)) as templates and Ni(NO(3))(2)·6H(2)O as the transition-metal source. Their frameworks are built with Ge(10) clusters and [Ni(en)(2)](2+) complexes. In both structures, Ge(10) clusters form square nets in the a-c plane, while the [Ni(en)(2)](2+) complexes bridge the square nets via Ni-O-Ge bonds to form 3D networks. They present the first examples to incorporate Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 33 publications
(18 reference statements)
1
19
0
Order By: Relevance
“…However, there are only a few inorganic examples reported with such mesopores, such as ITQ-43 [5] (a 28-ring germanium silicate), SU-M, [6] JLG-12 [7] (a 30-ring germanate), ITQ-37 [8] (a 30-ring germanium silicate), and NTHU-13, [9] a series of gallium zincophosphites with ring sizes from 24-ring to 72-ring. [7,18] Vanadoborates are interesting compounds assembled from vanadoborate clusters. Several strategies [9,13] have been proposed to circumvent this challenge.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are only a few inorganic examples reported with such mesopores, such as ITQ-43 [5] (a 28-ring germanium silicate), SU-M, [6] JLG-12 [7] (a 30-ring germanate), ITQ-37 [8] (a 30-ring germanium silicate), and NTHU-13, [9] a series of gallium zincophosphites with ring sizes from 24-ring to 72-ring. [7,18] Vanadoborates are interesting compounds assembled from vanadoborate clusters. Several strategies [9,13] have been proposed to circumvent this challenge.…”
mentioning
confidence: 99%
“…Müller et al [14] and Khan [15] introduced linkages between isolated cluster compounds to create porosity, while FØrey [16,17] proposed the scale chemistry method and predicted that the larger the structure building unit (SBU), the larger the pores. [7,18] Vanadoborates are interesting compounds assembled from vanadoborate clusters. Of these three strategies, the first two are very successful with cluster-based building units, such as the germanates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Yu and co‐workers have shown that a chiral metal complex cation can transfer its chirality to the inorganic framework through host‐guest hydrogen bonding interactions 12. To date, several open‐framework germanates have been synthesized by using metal complexes as the SDA's, including FJ‐6,6 JU‐82,3d ICMM‐2,13 |[In(dien) 2 ] 0.5 (H 3 dien) 0.5 (H 2 O) 2 |[Ge 7 O 14 F 3 ],14 FJ‐1,15 SUT‐1, SUT‐2,16 and JU‐63 (also known as CJ63) 17…”
Section: Introductionmentioning
confidence: 99%
“…Of these three strategies, the first two are very successful with cluster-based building units, such as the germanates. [7,18] Vanadoborates are interesting compounds assembled from vanadoborate clusters. Four types of vanadoborate clusters and their derivatives with different connections of VO 5 and BO 3 /BO 4 polyhedra are mainly reported: V 6 B 20 , [19,20] V 10 B 28 , [21,22] V 12 B 18 , [23][24][25] and V 12 B 16 [23, 26, 27] ( Figure 1).…”
mentioning
confidence: 99%